Pengembangan Potensi Ekowisata Suku Sambori Bima Nusa Tenggara Barat Indonesia - Zulharman, Zulharman; Noeryoko, Mochamad; Khaldun, Ibnu (Jurnal Ilmiah Mandala Education (JIME), 2021)
The objectives of this study were: a. Identifythe potential for ecotourism based on family medicinal plants (toga) that can be developed in Sambori Tribe b. Identify the right strategy for developingecotourism based on family medicinal plants (toga) in Sambori Tribe based on community and stakeholder perceptions. Research Methods:The research method used descriptive methods with survey and observation techniques. Data collection used purposive sampling, the data consisted of aspects of tourism products and markets, economic and business benefits from ecotourism activities and the socio-economic conditions of the community. Product aspects include the main potential of flora, namely toga plants, fauna, natural attractions and landscapes, amenities, accessibility and the socio-cultural life of the community. The market aspect consists of potential tourists in Sambori Tribe. Key informants (Stakeholders). In this study, thestrategy is not only subjective to the researcher, the researcher also involves the opinions of related experts to become respondents. Results and Discussion:  The results of the research that Sambori Tribe had a variety of toga plants with  the potential as a tourist attraction.Sambori Tribe has a diversity of flora and fauna potentials as well as a very suitable landscape potential as a tourist attraction. Conclusion: Sambor Tribe has the potential of flora and faund and the landscape.  The future strategy for developing ecotourism of Toga in Sambori Tribe includes optimizing the potential of toga plants in terms of cultivation, land management and processing potential of toga plants, developing high potential of biological natural resources, both flora and fauna, and natural panoramas